2002
DOI: 10.1128/jcm.40.3.794-798.2002
|View full text |Cite
|
Sign up to set email alerts
|

Food-Borne Outbreak of Gastroenteritis Associated with Genogroup I Calicivirus

Abstract: An outbreak of gastroenteritis affecting 158 of 219 (72%) guests and employees at a hotel is described. Food served at the hotel restaurant is believed to have been the source of the outbreak and to have been contaminated by sick employees working in the restaurant. A secondary attack rate of 22% was seen involving 43 persons in all. In stool specimens from seven of eight patients, Norwalk-like viruses (NLVs) were detected by electron microscopy. While NLV-specific PCR using primers JV12 and JV13 were negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…In restaurant J, frozen imported bivalve shellfish was initially suspected as the cause of infection, but no NV was detected in either the shellfish or other food samples. In outbreaks originating from infected food handlers, specific food is not always identified as the main source of the infection (5,12,15). Lopman et al (19) have recently reported that specific vehicles were implicated in 39.1% of NV food-borne outbreaks and that multiple food vehicles contributed to some outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In restaurant J, frozen imported bivalve shellfish was initially suspected as the cause of infection, but no NV was detected in either the shellfish or other food samples. In outbreaks originating from infected food handlers, specific food is not always identified as the main source of the infection (5,12,15). Lopman et al (19) have recently reported that specific vehicles were implicated in 39.1% of NV food-borne outbreaks and that multiple food vehicles contributed to some outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the GII/4 strains are an important cause of both outbreaks and sporadic occurrences of gastroenteritis. Noroviruses can be transmitted by the fecal-oral route through person-to-person contact and by food-and waterborne infections (2,3,12). In Japan, oyster-associated gastroenteritis is a major problem, and it is not unusual to detect multiple norovirus genotypes in an oyster-associated outbreak (14).…”
Section: Discussionmentioning
confidence: 99%
“…The prototype strain of human norovirus is the Norwalk virus (NV/Human/US/1968), which was first discovered in an outbreak of gastroenteritis in an elementary school in Norwalk, OH, in 1968 (15). Noroviruses are the leading cause of outbreaks of gastroenteritis in the world; they cause outbreaks in various settings, including hospitals, cruise ships, schools, and restaurants (2,9,12,15,23,24,29). In addition, noroviruses have been detected in environmental samples (e.g., treated and untreated sewage) as well as in contaminated foods such as oysters, shellfish, sandwiches, salads, raspberries, and even ice (7,18,19,26).…”
mentioning
confidence: 99%
“…In recent years, caliciviruses have emerged as an important cause of gastroenteritis in all age groups and are now recognized as the main cause of gastroenteritis in nursing homes and hospitals (3,8,12,14,15,27).…”
mentioning
confidence: 99%